(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: As the number of older people is increasing, also the need for professional sports instructors is growing. Volunteers have an important role in supporting active ageing as peer instructors or outdoor friends. Project or Policy Description. Development. The Strength in Old Age Programme (2004–) in Finland aims to launch health-enhancing exercise for independently living older adults with decreased functional capacity. The Coordinator, The Age Institute, offers courses that enable and support the professionals to locally train volunteers to act as peer instructors for exercise groups and outdoor friends. Peers learn how to instruct strength and balance exercises and outdoor friends how to support outdoor activities. Implementation. The training course is free of charge for the municipalities belonging to the Strength in Old Age Programme. The participants receive readymade material they can use as well as practical tips for the local training. Until now, there are over 1,600 trainers and over 6,000 peers and outdoor friends trained. However, new volunteers are needed. Evaluation. A survey was disseminated broadly to volunteers to examine their motivations and perceived benefits of serving as peer instructors or outdoor friends. We received 291 responses. The survey was openly shared through networks, and no response rate was available. The most common motivators were relevance of helping others (36%), being asked to become a volunteer (19%), getting exercise during volunteering (17%), and having more time after retirement (17%). The volunteers perceived mostly good or strong benefits from their activity. Volunteering has generated positive emotions (97%) and offered something meaningful to do (95%). The best thing about volunteering is togetherness (42%). Only 8% said that the activity had been a burden. Dissemination. The results will be disseminated through the future activities in Strength in Old Age Programme, which enable the professionals’ knowledge how to better support volunteers and attract new volunteers to participate. The survey will be complemented by interviews of volunteers. Conclusions: To develop local sports activities, training and supporting volunteers is important. It is a cost-effective way to keep old adults fit and it also improves the wellbeing of volunteers. Keywords: Active ageing, peer instructor, outdoor friend, volunteer